There is no future for the workplace. - Challenger, John (Public Management (00333611), 1999)
A reprint from the October 1998 issue of The Futurist magazine, Bethesda, Maryland. The current trends in population and technology challenge U.S. cities to reconsider their goals for education and work. The U.S. cannot hope to sustain economic growth over the coming 25 years unless it guarantees that every able-bodied person can effectively participate in that growth. The trends in population and technology are discussed.